A comparative study of evaluate dose related feto-maternal effects of syntocinon during labor - Radhanpuri, Farhin; Sharma, Jyoti; Desai, Deepak A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In times, Active management of Third stage is a gold standard rule, to reduce third stage complications. In the same tradition, we conceived the idea of “Active management of Labor”, as a whole, to reduce all the problems, maternal and fetal, to a minimum possible level. With this motto, and aim in mind we devised the protocol of study I present forthwith. Methods: This study was done in Dhiraj Hospital in Obstetrics and Gynaecology department. The study duration was 1 year. It was a comparative study comprising of patients who came in labor room under unit 3 included in group 1 and under other units included in group 2 and 3. In this study, those patients were augmented who came to labor room. These patients were studied after screening inclusion and exclusion criteria & its outcome was assessed. Results: Augmentation-delivery interval in primigravida was 4.5 hours in group 1, in group 2 it was 3 hrs, where as in group 3 active phase delivery interval was 8.1 hours, Augmentation-delivery interval in multigravida was 3.5 hours in group 1, in group 2 it was 3 hrs, where as in group 3 active phase delivery interval was 6 hours. The incidence of spontaneous vaginal delivery was higher in group 1 than in group 2 and 3. There was very less or absent of maternal complications observed in group 1 than in other 2 groups. Incidence of NICU admissions was only 1 % in group 1, whereas in other groups it was higher. There was no neonatal mortality noted in either group. Conclusions: There is significant reduction in the duration of labor by augmenting labor with slow low regulated dose of syntocinon drip, thus reducing the maternal exhaustion and morbidity due to prolonged labor. There is significant reduction in the operative interference like LSCS, vacuum and forceps delivery, thus reducing maternal morbidity associated with operative interference and anesthesia. It also reduces the cost of medical services. The incidence of fetal distress and LSCS for the same does not increase in the augmentation group, indicating that syntocinon can be safely used for the augmentation. At this time, much attention in the field of obstetrics is focused on attempting to reduce the rate of cesarean section, not only to reduce maternal morbidity, but to lower the cost of medical care. Our finding is that syntocinon administration can significantly reduce the cesarean section rate.